Time Domain Characterization of 1-2 GHz Circular-ended Bowtie Antenna Using Normalizad Impulse Response - Suryana, Joko; Suksmono, Andriyan B.; Mengko, Tati R. (Makara Journal of Technology, 2005)
Time Domain Characterization of 1-2 GHz Circular-ended Bowtie Antenna Using Normalizad Impulse Response. Frequency domain analysis is a powerful and compact tool for characterizing the antenna parameters such as gain, radiation pattern and the impedance as a function of frequency. However, if time or space is a major concern, such as in the GPR appication, the time domain analysis would be a very important tool due to their unique capability for determining the echo delay and range profile of target image. In this paper, we will describe the classical theory of system characterization in time domain, and then also propose the mathematical model for characterizing the 1 – 2 GHz circular-ended Bowtie antenna. From the measurement results, we concluded that the implemented Bowtie antenna has good normalized impulse response with very small ringing, so it is suitable for GPR applications.